Magnetic Resonance Thrombus Imaging to Differentiate Acute from Chronic Portal Vein Thrombosis - van Dam, Lisette F.; Klok, Frederikus A.; Tushuizen, Maarten E.; Ageno, Walter; Darwish Murad, Sarwa; van Haren, Guido R.; Huisman, Menno V.; Lauw, Mandy N.; Iglesias del Sol, Antonio; Wasser, Martin N.J.M.; Willink, Ysbrand; Kroft, Lucia J.M. (TH Open, 2020)
Introduction Timely diagnosis and treatment of portal vein thrombosis (PVT) is crucial to prevent morbidity and mortality. However, current imaging tests cannot always accurately differentiate acute from chronic (nonocclusive) PVT. Magnetic resonance noncontrast thrombus imaging (MR-NCTI) has been shown to accurately differentiate acute from chronic venous thrombosis at other locations and may also be of value in the diagnostic management of PVT. This study describes the first phase of the Rhea study (NTR 7061). Our aim was to select and optimize MR-NCTI sequences that would be accurate for differentiation of acute from chronic PVT.Study Design The literature was searched for different MRI sequences for portal vein and acute thrombosis imaging. The most promising sequences were tested in a healthy volunteer followed by one patient with acute PVT and two patients with chronic PVT, all diagnosed on (repetitive) contrast-enhanced computed tomography (CT) venography to optimize the MR-NCTI sequences. All images were evaluated by an expert panel.Results Several MR-NCTI sequences were identified and tested. Differentiation of acute from chronic PVT was achieved with 3D T1 TFE (three-dimensional T1 turbo field echo) and 3D T1 Dixon FFE (three-dimensional T1 fast field echo) sequences with best image quality. The expert panel was able to confirm the diagnosis of acute PVT on the combined two MR-NCTI sequences and to exclude acute PVT in the two patients with chronic PVT.Conclusion Using 3D T1 TFE and 3D T1 Dixon FFE sequences, we were able to distinguish acute from chronic PVT. This clinical relevant finding will be elucidated in clinical studies to establish their test performance.
Keywords: diagnosis; diagnostic imaging; magnetic resonance imaging; venous thrombosis